Topological Mappings Based on SPG*-Closed Set - Prof. Dr. Ali khalaf hussain; Munther Hassan, Marwa (Wasit Journal of Computer and Mathematics Science, 2022)
In this paper, we introduce the concept of SPG*-closed mapping and continuous mapping among which SPG-closed mappings, SPG*-closed mappings and SPG**-closed mappings and the relationship between them, and also SPG-continuous mappings, SPG*-continuous mappings and SPG**-continuous mappings and the relationship between them. Among the result we obtain are the concepts of SPG**-closed mappings and closed mappings are independent also PG**-continuous mappings and continuous mapping are independent.